Rancang Bangun Sistem Penjualan Busana Muslim Berbasis Website Menggunakan Metode RAD Studi Kasus Toko Raihan Collection - Raihan, Muhammad; Shadam, Muhammad; Saprudin (CV. Shofanah Media Berkah, 2025)
The rapid development of internet technology has encouraged many businesses, including small and medium enterprises (SMEs), to transition to web-based sales. This study aims to design and develop a web-based sales system for Muslim fashion using the Rapid Application Development (RAD) method at Raihan Collection Store. The RAD method was chosen for its flexibility in adapting to user needs and accelerating the development process. The designed system includes features such as product catalogs, product details, automated stock management, and online transactions to enhance operational efficiency and expand market reach. The implementation of this system demonstrated improvements in stock management efficiency, ease of access to product information, and transaction flexibility. This study significantly contributes to supporting the digitalization of SMEs and provides guidance for future web-based e-commerce system development.